2008
DOI: 10.1037/1528-3542.8.2.192
|View full text |Cite
|
Sign up to set email alerts
|

The impact of changes in spatial distance on emotional responses.

Abstract: Drawing on motivational approaches to emotion, the authors propose that the perceived change in spatial distance to pictures that arouse negative emotions exerts an influence on the significance of these pictures. Two experiments induced the illusion that affective pictures approach toward the observer, recede from the observer, or remain static. To determine the motivational significance of the pictures, emotional valence and arousal ratings as well as startle responses were assessed. Approaching unpleasant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 27 publications
11
63
0
Order By: Relevance
“…Our results are in line with a recent study that could demonstrate that changes in spatial distance, in this case the illusion of a movement towards or away from the participant, can increase the motivational effects of emotional stimuli on the startle response (Muhlberger, Neumann, Wieser, & Pauli, 2008). However, the stimuli in our study remained static and did not respond to the motor action of the participant.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in line with a recent study that could demonstrate that changes in spatial distance, in this case the illusion of a movement towards or away from the participant, can increase the motivational effects of emotional stimuli on the startle response (Muhlberger, Neumann, Wieser, & Pauli, 2008). However, the stimuli in our study remained static and did not respond to the motor action of the participant.…”
Section: Discussionsupporting
confidence: 92%
“…Mühlberger, Neumann, Wieser, and Pauli (2008) found that approaching (growing in size) unpleasant images evoked increased physiological arousal compared to the same picture moving away (shrinking in size). A similar effect was found when only the mental representation of looming was manipulated (Davis, Gross, and Ochsner, 2011).…”
Section: Spatial Distancementioning
confidence: 94%
“…Magnitudes were calculated for the three categories. Participants with mean magnitudes below 5 μV across all trials were coded as non-responders and excluded from further analyses; therefore, 4 depressive patients and 2 healthy controls from the original sample were eliminated [43]. …”
Section: Methodsmentioning
confidence: 99%